Application of a Novel Semiconductor Catalyst, CT, in Degradation of Aromatic Pollutants in Wastewater: Phenol and Catechol. (14th April 2014) - Chen, Xiao; Zhang, Yanling; Zhou, Xuefei; Ichimura, Shoji; Tong, Guoxiu; Zhou, Qiming; Chen, Xi; Wang, Wenzhao; Liang, Yan
Abstract : Water-soluble phenol and phenolic compounds were generally removed via advanced oxidation processes. A novel semiconductor catalyst, CT, was the first-time employed in the present study to degrade phenol and catechol. The phenolic compounds (initial concentration of 88 mg L −1 ) were completely mineralized by the CT catalytic nanoparticles (1%) within 15 days, under acidic condition and with the presence of mild UV radiation (15 w, the emitted wavelength is 254 nm and the light intensity <26  μ w/cm 2 ). Under the same reaction condition, 1% TiO2 (mixture of rutile and anatase, nanopowder, <100 nm) and H2 O2 had lower removal efficiency (phenol: <42%; catechol: <60%), whereas the control (without addition of catalysts/H2 O2 ) only showed <12% removal. The processes of phenol/catechol removal by CT followed pseudo-zero-order kinetics. The aromatic structures absorbed the UV energy and passed to an excited state, which the CT worked on. The pollutants were adsorbed on the CT's surface and oxidized via charge-transfer and hydroxyl radical generation by CT. Given low initial concentrations, a circumstance encountered in wastewater polishing, the current set-up should be an efficient and less energy- and chemical-consumptive treatment method.